Mother’s Milk Supplementation and 6-Months Exclusive Breastfeeding in Cipayung Sub-District, Depok City, Indonesia: A Quasi-Experimental Study - Fikawati, S.; Nopiyanti, A.; Syafiq, A.; Bakara, S.M. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Calorie intake during lactation is not being paid sufficient attention despite its importance to support the success of 6-months exclusive breastfeeding (EBF). In Indonesia, lactating mother’s calorie intake is low. The objective of this study was to determine the effect of calorie supplementation on the success of 6-month EBF. Materials and Methods: Four groups of lactating mothers in Cipayung Sub-district, Depok City, Indonesia were purposively selected and followed up for 6 months. The first group received calorie supplementation in the form of one glass of milk per day (140 kcal per day) five days a week for 3 months. Cadres provided milk supplementation and ensured complete consumption. The second group received reminder message from cadres, the third group received EBF short message service and the fourth group was a control group. All groups were observed and measured on the status of breastfeeding, anthropometry and food consumption monthly. Results: The calorie intake of those who were successful in EBF was significantly higher than those who failed. Milk supplementation is the dominant factor for the success of 6-months EBF. The milk supplementation group had the highest percentage of mothers who were successful in providing 6-months EBF. Conclusion: The study has proven significant role of milk supplementation to support EBF. Provision of one glass of milk five times a week for 3 months could increase EBF prevalence to 90%, compared to 60% among other groups. Milk supplementation for lactating mothers must be considered as one strategy to increase the prevalence of 6 months EBF in Indonesia.